USE OF ELECTRONIC REGISTRATION IN TUBERCULOSIS DETECTION: POTENTIALS AND DIFFICULTIES ACCORDING TO PROFESSIONALS - Jéssica Oliveira Tomberg; Roxana Isabel Cardozo Gonzales; Lílian de Moura Lima Spagnolo; Dagoberta Alves Vieira; Jenifer Harter; Javier Roger Raul Vargas Herrera (Universidade Federal do Paraná, 2018)
Objective: identify the potentials and difficulties in the use of a computerized registration system to detect tuberculosis cases in primary health care. Method: intervention study in the cities of Sapucaia and Pelotas, Rio Grande do Sul, between 2013 and 2014, involving the implementation of a computerized registration system at the primary health care services, followed by a qualitative interview. For the data analysis, Bardin's Thematic Content Analysis technique was applied. Results: three analysis categories were identified: Agility in the monitoring of respiratory symptomatics, Engagement and sensitization of professional and Difficulties faced in the use of the information system. Final considerations: the computer system enhanced the agility of the registration, the communication between health professional and services and reflections on tuberculosis care. The difficulties were related to the physical and organizational structure of the primary health care services.